2002
DOI: 10.1177/174182670200900610
|View full text |Cite
|
Sign up to set email alerts
|

Random Capillary Blood Sugar and Coronary Risk Factors in a South Kerala Population

Abstract: Background High prevalence of type 2 diabetes in one subdivision of a district in south India prompted us to look at the prevalence of other major coronary risk factors, and relate these to random blood sugar values.Design Cross-sectional survey of all adult residents of four wards (clusters of households) of a subdivision. Detailed investigation for diabetes and blood lipids in a selected subsample with random blood sugar (RBS) 4109 mg/dl by glucometer.Methods From the selected wards, we conducted a standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…[1] Researchers from south India reported 37% prevalence of hypertension in 30-64 age group. [12] Gupta from Jaipur, through three serial epidemiological studies (Criteria: ≥140/90 mm of Hg) carried out during 1994, 2001, and 2003 demonstrated rising prevalence of hypertension (30%, 36%, and 51%, respectively, among males and 34%, 38%, and 51% among females). [4] In 2002, Hazarika et al reported 61% prevalence (criteria:=JNC VI) of hypertension among aged 30 and above of both sexes in Assam.…”
Section: Discussionmentioning
confidence: 98%
“…[1] Researchers from south India reported 37% prevalence of hypertension in 30-64 age group. [12] Gupta from Jaipur, through three serial epidemiological studies (Criteria: ≥140/90 mm of Hg) carried out during 1994, 2001, and 2003 demonstrated rising prevalence of hypertension (30%, 36%, and 51%, respectively, among males and 34%, 38%, and 51% among females). [4] In 2002, Hazarika et al reported 61% prevalence (criteria:=JNC VI) of hypertension among aged 30 and above of both sexes in Assam.…”
Section: Discussionmentioning
confidence: 98%
“…19 Later studies in Kerala reported 49% prevalence of overweight among 30-64 age group in 1998 and 41% among 40-60 age group during 2000. 20,21 ICMR Task force study (1994) reported a higher prevalence in urban Delhi (31%) and a lower prevalence in rural Haryana(8%) using the criteria (WC >94 cm among men and >88 cm among women). 17 The Sentinel surveillance on CVD in Indian industrial population (2001-03), using modified ATP III criteria for Asian (WC >90 cm among men and >80 cm among women) reported an overall prevalence of abdominal obesity at 32%.…”
Section: Discussionmentioning
confidence: 99%
“…India is the diabetes capital of the world with the disease estimated to affect 6.5 to 19.5% of the adult Indians [7]. The situation is worse in the South Indian state of Kerala where the prevalence is the maximum among all Indian states [8]. The relation between diabetes and thyroid dysfunction has been studied by various researchers and the prevalence of hypothyroidism among patients with diabetes is reported from 4.8 to 31.4% [9].…”
Section: Introductionmentioning
confidence: 99%